Broadband and high-efficient reflective linear-to-circular polarizer with Wi-Fi shaped metasurface. (11th August 2022) - Tian, Feng; Wang, Yuxiang; He, Jiahao; Hao, Han; Ma, Xia; Huang, Xiaojun
Abstract: Arbitrarily manipulating the polarization states of electromagnetic waves has gained interest due to its wide application in modern wireless communication systems. However, conventional polarizers face major bottlenecks such as bulky size, low efficiency and narrow frequency band. This paper proposes a reflective linear-to-circular polarizer using Wi-Fi shaped metasurface, and the designed polarizer can efficiently convert the linearly polarized incident waves into nearly perfect circularly polarized reflected waves in wideband frequency region of 12.1–20 GHz. Based on simulations, the polarizer has an axial ratio of ⩽3 dB at 12.1–20 GHz and a relative bandwidth of 49.2%. The polarization conversion rate is over 97% in 12.1–20 GHz. The physical analysis of the polarization conversion is based on the surface current distributions. To validate the simulations, microwave tests are carried out, and the theory, simulations, and experiments all accord quite well.